Short and Diastereoselective Total Synthesis of the Polyhydroxylated Pyrrolidine LAB-1: A Potent α-Glycosidase Inhibitor - da Silva, Erica C.; Yamakawa, Nathália C. G.; Dos Santos, Alcindo A.; Coelho, Fernando (Synthesis, 2017)
We described herein a total synthesis of 1,4-dideoxy-1,4-imino-l-arabinitol [(2S,3S,4S)-2-(hydroxymethyl)pyrrolidine-3,4-diol, LAB-1], a polyhydroxylated pyrrolidine, which has been demonstrated to be a selective and potent α-glycosidase inhibitor. The main features of our approach are its shortness, efficiency, and simplicity. The total synthesis was accomplished in 6 steps with an overall yield of 12%, starting from a chiral optically active Morita–Baylis–Hillman (MBH) adduct prepared (without epimerization), from Garner’s aldehyde. As far as we know, this is the first report describing the total synthesis of this biologically active pyrrolidine by exploring the synthetic versatility of a MBH adduct.
Keywords: LAB-1; iminosugars; pyrrolidine; Morita–Baylis–Hillman